Aplikasi Kamus Simplisia Dan Resep Obat Tradisional (Sidota) Berbasis Android - Lailatul Lutfiah (Jurnal Sains dan Informatika, 2022)
Simplicia is a natural ingredient used in the manufacture of traditional medicine, in this pandemic era, many families prefer to consume herbal medicine instead of going to the doctor because they are worried about contaminated by Covid. By utilizing an Android Smartphone that almost all people have, SIDOTA's goal is to provide information on the correct processing of simplicia and can get maximum medicinal effects. In addition, SIDOTA can facilitate the learning process of Pharmacy students or students majoring in Pharmacognosy subjects or subjects. In this paper, the writer used the Waterfall method for the development method, with the Analysis, Design, an Implementation of the design. This application displays simplicia information data as well as recipes and ways of making traditional medicines.